Analysis of upper and middle segment esophageal setup errors and planning of target margins based on cone beam computed tomography for esophageal radiation with immobilized thermoplastic film. Issue Volume 3:Issues 1(2019) (25th February 2019) - Yong, Shi; Ying, Chen; Fen, Zhang; Ling, Li; Yanli, Liu; Qinying, Yan; Min, Zhang; Chengjian, Li; Dong, Li
Abstract: Objective: To evaluate the setup errors in patients with upper and middle segment esophageal cancer who underwent cone beam computed tomography immobilized by thermoplastic film, and to probe the margins using the esophageal clinical target volume (CTV) in three directions. Methods: A total of 60 patients with upper and middle segment esophageal cancer were enrolled. All patients were immobilized by thermoplastic film and underwent cone beam computed tomography at the first, 10th, and 20th treatment after positioning, respectively. These cone beam computed tomography images were registered to the planning computed tomography to determine setup errors in translational and rotational directions. Then, CTV margins were calculated from the systematic and random errors. Results: Setup errors on x (left–right), y (superior–inferior), and z (anteroposterior) translational directions were 2.93 ± 2.24, 3.81 ± 2.31, and 2.41 ± 1.65 mm, and on θ (pitch degree), ϕ (roll degree), and ψ (yaw degree) rotational directions were 2.08 ± 1.32°, 1.53 ± 1.03°, and 1.65 ± 1.14°, respectively. The margins from CTV were 7.35, 8.09, and 5.94 mm in the x, y, and z directions, respectively. In the y and z directions, translational errors were significantly correlated with ϕ and ψ degree rotational errors (Pearson = –0.511, –0.503, P < 0.05). In the interfraction, only on the z direction, setup changes were considered significantly correlated with ψ degree (Pearson = –0.571, P < 0.05). Conclusions: In patients with upper and middle segment esophageal cancer immobilized by thermoplastic film, the margins from CTV were recommended to be not less than 7.39, 7, 83, and 5.91 mm in x, y, and z directions, respectively. The position immobilization method and positioning workflow should be improved further to reduce the influence of breathing movement on setup errors.